Taccalonolides: Structure, semi-synthesis, and biological activity - Li, Yan; Du, Yu-Feng; Gao, Feng; Xu, Jin-Bu; Zheng, Ling-Li; Liu, Gang; Lei, Yu (Frontiers in Pharmacology, 2022)
Natural products produced by plants have been the backbone for numerous anti-cancer agents. Among the most successful anti-cancer drugs, microtubule-targeting agents (MTAs) like vinca alkaloids, especially vinblastine and vincristine, and the taxanes, especially paclitaxel and docetaxel, are plant-derived compounds. The microtubule stabilizers paclitaxel and docetaxel are used principally for solid tumors, including breast, ovarian, non-small cell lung cancers as well as head and neck tumors. Taccalonolides isolated from plants of the genus Tacca are a series of highly oxygenated pentacyclic steroids. Taccalonolides not only exhibit the similar microtubule stabilizing activity as famous anti-tumor drugs paclitaxel and epothilone, but also reverse the multi-drug resistance of paclitaxel and epothilone in cellular and animal models. They have attracted numerous attentions in the fields of medicinal chemistry and biochemistry due to their diverse structures, unique mechanism of action, and low toxicity. The present review is focused on the structural classification, modification, semi-synthesis, and pharmacological mechanism of taccalonolides. It is hoped that this systematically summary of taccalonolides can provide new ideas for researchers engaged in the related fields and potential lead conpounds for the discovery of microtubule stabilizing anti-tumor drugs.